Evaluating the Susceptibility of Different Crops to Smoke Taint - Julie Culbert; Renata Ristic; Kerry Wilkinson (Horticulturae, 2024)
The potential for grapes and wine to be tainted following vineyard exposure to wildfire smoke is well established, with recent studies suggesting hops and apples (and thus beer and cider) can be similarly affected. However, the susceptibility of other crops to ‘smoke taint’ has not yet been investigated. Smoke was applied to a selection of fruits and vegetables, as well as potted lavender plants, and their volatile phenol composition determined by gas chromatography–mass spectrometry to evaluate their susceptibility to contamination by smoke. Volatile phenols were observed in control (unsmoked) capsicum, cherry, lavender, lemon, spinach and tomato samples, typically at ≤18 µg/kg, but 52 µg/kg of guaiacol and 83–416 µg/kg of o- and m-cresol and 4-methylsyringol were detected in tomato and lavender samples, respectively. However, significant increases in volatile phenol concentrations were observed as a consequence of smoke exposure; with the highest volatile phenol levels occurring in smoke-exposed strawberry and lavender samples. Variation in the uptake of volatile phenols by different crops was attributed to differences in their physical properties, i.e., their surface area, texture and/or cuticle composition, while the peel of banana, lemon, and to a lesser extent apple samples, mitigated the permeation of smoke-derived volatile phenols into pulp. Results provide valuable insight into the susceptibility of different crops to smoke contamination.